Rural Employment in Africa : Trends and Challenges - Christiaensen, Luc; Maertens, Miet (Washington, DC: World Bank, 2022)
Africa’s rural population continues to expand rapidly and labor productivity in agriculture and many rural off farm activities remains low. This paper uses the lens of a dual economy and the associated patterns of agricultural, rural, and structural transformation to review the evolution of Africa’s rural employment and its inclusiveness. Many African countries still find themselves in an early stage of the agricultural and rural transformation. Given smaller sectoral productivity gaps than commonly assumed, greater size effects and larger spillovers, investment in agriculture and the rural off-farm economy remains warranted to broker the transition to more and more productive rural employment. The key policy questions thus become how best to invest in the agri-food system (on and increasingly also off the farm) and how best to generate demand for nonagricultural goods and services which rural households can competitively produce. Informing these choices continues to present a major research agenda, with digitization, the imperative of greening and intra-African liberalization raising many unarticulated and undocumented opportunities and challenges.